PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, SOLVABILITAS DAN DEBT DEFAULT TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2009-2013 - KARINA A, PUTRI (Jurnal Akuntansi AKUNESA, 2015)
The aim of the research is to analyze the factors that cause the reception of audit opinion going concern in the manufacturing companies in Indonesia. The independent variables used are firm size, profitability, solvability, debt default and the dependent one is audit going concern opinion.The research design applied in this study was quantitative research by using logistic regression. The sample observed were the manufacturing companies listed on the Indonesian stock exchange in the period 2009-2013. The method used for the sampling was purposive sampling, so that the samples obtained during observation were 335 companies.The result of the research indicated that the solvability measured by Debt to Total Asset Ratio (DAR) and debt default positively affected to the reception of audit opinion going concern. However, the firm size measured by total assets and profitability which was connected to the Return on Assets (ROA) did not take effect on the reception of audit going concern opinion. Key words: Audit going concern opinion, Firm size, Profitability, Solvability, and Debt default.